Effects of Oil Shocks on the Trade Balance of Azerbaijan: Evidence from the TVP-VAR Model - Çatik, Abdurrahman Nazif; Balli, Esra; Arıca, Emre Umut; Makhmudov, Samariddin; Sultanova, Sevara; Uktamova, Nozima (International Journal of Energy Economics and Policy, 2025)
This study examines the effect of oil shocks on Azerbaijan’s trade balance using a Time-Varying Parameter Vector Autoregression (TVP-VAR) model, drawing on monthly data from December 1994 to November 2024. The results indicate that the negative effects of oil production shocks on Azerbaijan’s trade balance exhibit considerable variation over time and that these adverse impacts become statistically significant in the post-COVID-19 period, indicating a heightened sensitivity of the trade balance to oil production fluctuations in the wake of the pandemic. Although the time-varying responses to oil price shocks are generally positive, they lose statistical significance during periods of sharp decline, suggesting a weakening of the transmission mechanism under extreme market conditions. The impact of exchange rate misalignment on the trade balance fluctuates, showing positive responses following major devaluation or policy changes. This study underscores the necessity of reducing dependence on oil exports and diversifying public revenues to lessen reliance on oil. These results provide important information for controlling external balances in nations that rely heavily on natural resources.